Active Learning Strategies: A Mini Review of Evidence-Based Approaches - Martinez, Maria Eugenia; Gomez, Valeria (Acta Pedagogia Asiana, 2025)
Active learning strategies such as think-pair-share (TPS), problem-based learning (PBL), flipped classrooms, and collaborative projects are essential for promoting student engagement, critical thinking, and academic success. This review brings together evidence from multiple disciplines to examine the effectiveness of these strategies and their impact on educational outcomes. PBL is particularly popular in fields such as engineering and medicine, where it enhances problem-solving, self-directed learning, and teamwork by exposing students to real-world, interdisciplinary challenges. Flipped classrooms, where content delivery occurs outside of the classroom, can enable more interactive, discussion-based learning in class, which can improve student performance and satisfaction, despite challenges associated with preparation and varying learning rates. Collaborative projects are often used in economics and social sciences to foster important skills such as teamwork, leadership, and communication through group interaction. The effectiveness of these strategies is further enhanced by structured instructional models such as the analysis, design, development, implementation, and evaluation (ADDIE) framework, ensuring alignment with educational goals. In addition, the incorporation of artificial intelligence into active learning is transforming educational practice by providing personalized learning experiences and immediate feedback, although it also raises ethical concerns about the balance between technology and human interaction. In summary, active learning strategies, if carefully implemented, can provide students with important skills for academic and career success while meeting the changing demands of modern education.